Cytomegalovirus infection and graft rejection as risk factors for pneumocystis pneumonia in solid organ transplant recipients: A systematic review and meta‐analysis. Issue 8 (16th July 2018) - Hosseini‐Moghaddam, Seyed M.; Krishnan, Rohin Jayaram; Guo, Hui; Kumar, Deepali
Abstract: A growing number of publications have reported the outbreaks of post‐transplant pneumocystis pneumonia (PJP). In most studies, the onset of PJP was beyond 6‐12 months of prophylaxis. Cytomegalovirus (CMV) infection and allograft rejection have been repeatedly reported as probable risk factors for post‐transplant PJP. In this systematic review and meta‐analysis, we determined the pooled effect estimates of these 2 variables as risk factors. Data sources included PUBMED, MEDLINE‐OVID, EMBASE‐OVID, Cochrane Library, Networked Digital Library of Theses and Dissertations, World Health Organization, and Web of Science. We excluded publications related to hematopoietic stem cell transplantation (HSCT) or Human Immunodeficiency Virus (HIV) patients. Eventually, 15 studies remained for the final stage of screening. Cytomegalovirus infection (OR: 3.30, CI 95%: 2.07‐5.26, I 2 : 57%, P  = 0.006) and allograft rejection (OR:2.36, CI95%: 1.54‐3.62, I2: 45.5%, P  = 0.05) significantly increased the risk of post‐transplant PJP. Extended prophylaxis targeting recipients with allograft rejection or CMV infection may reduce the risk of PJP.